Community Empowerment as a Tourist Attraction and Creative Economy Development in Kota Tua Jakarta - Setiawati, Rahmi (Journal of Indonesian Tourism and Policy Studies, 2020)
The Kota Tua Jakarta area is one of the leading tourist attractions in DKI Jakarta Province based on cultural heritage. Currently, the City Government of DKI Jakarta has carried out a revitalization, namely the construction of a rearrangement of the old city, so that it becomes an urban tourism area in the past (history). The purpose of this research is to build a community empowerment program as a tourist attraction and create a creative economy in Kota Tua. The concepts used are empowerment, community, attraction and creative economy. The research method used is a qualitative approach with data collection techniques through interviews, observation and literature study. This research resulted in a community empowerment program, namely building community awareness and communication in creating economic improvements for the welfare of communities around Kota Tua. To realize the need for community information community mapping, namely the initial stage of conducting initial mapping of communities in Kota Tua, designing community empowerment for economic improvement and building the community's creative economy.